Effect of Core Training on Skill Performance Among Athletes: A Systematic Review - Luo, Shengyao; Soh, Kim Geok; Soh, Kim Lam; Sun, He; Nasiruddin, Nasnoor Juzaily Mohd; Du, Congxin; Zhai, Xiuwen (Frontiers in Physiology, 2022)
Background: This study aims to present a critical review of the existing literature on the effect of core training on athletes’ skill performance, and to provide recommendations and suggest future research directions for both coaches and researchers. Methods: The data in this study were reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. This review collected studies in the literature using prominent academic and scientific databases such as Ebscohost, Scopus, PubMed, Web of Science, and Google Scholar. Only 16 of the 119 studies met all of the inclusion criteria, and were thus included in the systematic review. Each study's quality was determined using the PEDro scale. The scoring of 16 studies ranges from 2 to 5. Results: Core training could potentially improve skill performance among football, handball, basketball, swimming, dancing, Karate, Muay Thai, gymnasts, volleyball, badminton, and golf players. Conclusion: Compared with the traditional training methods, core training is a new strength training method. Strong core muscles function as hubs in the biological motor chain, which create a fulcrum for the four limbs' strength and establish a channel for the cohesion, transmission, and integration of the upper and lower limbs. In other words, core training optimizes the transfer and overall control of motion and force to the terminal segment within athletic actions. Meanwhile, core training could increase stability and stiffness in the spine to reduce unrequired "energy leaks" and torso movement during the exertion of external loads. This mechanism could help athletes achieve better skill performance. Therefore, this review suggests that core training should be integrated into athletes' daily training routines.